Women and slavery in America : a documentary history - Lewis, Catherine M.; Lewis, J. Richard, 1967- (University of Arkansas Press, 2011)
Women and Slavery offers readers an opportunity to examine the establishment, growth, and evolution of slavery in the United States as it impacted women-enslaved and free, African American and white, wealthy and poor, northern and southern. The primary documents-including newspaper articles, broadsides, cartoons, pamphlets, speeches, photographs, memoirs, and editorials-are organized thematically and represent cultural, political, religious, economic, and social perspectives on this dark and complex period in American history. --From publisher's description.